Developing a reference material set for the magnetic properties of NdFeB alloy-based hard magnetic materials - E. A. Volegova; T. I. Maslova; V. O. Vas’kovskiy; A. S. Volegov (Стандартные образцы)
Introduction The introduction indicates the need for the use of permanent magnets in various technology fields. The necessity of measuring the limit magnetic hysteresis loop for the correct calculation of magnetic system parameters is considered. The main sources of error when measuring boundary hysteresis loops are given. The practical impossibility of verifying blocks of magnetic measuring systems element-by-element is noted. This paper is devoted to the development of reference materials (RMs) for the magnetic properties of hard magnetic materials based on Nd2Fe14B, a highly anisotropic intermetallic compound.Materials and measuring methods Nd-Fe-B permanent magnets were selected as the material for developing the RMs. RM certified values were established using a CYCLE‑3 apparatus included in the GET 198‑2017 State Primary Measurement Standard for units of magnetic loss power, magnetic induction of constant magnetic field in a range from 0.1 to 2.5 T and magnetic flux in a range from 1·10–5 to 3·10–2 Wb.Results and its discussion Based on the experimentally obtained boundary hysteresis loops, the magnetic characteristics were evaluated, the interval of permitted certified values was set, the measurement result uncertainty of certified values was estimated, the RM validity period was established and the first RM batch was released.Conclusion On the basis of conducted studies, the RM type for magnetic properties of NdFeB alloy-based hard magnetic materials was approved (MS NdFeB set). The developed RM set was registered under the numbers GSO 11059–2018 / GSO 11062–2018 in the State RM Register of the Russian Federation.